Gender Marginalisation in Indian Society: Inequalities and Cultural Exclusion of Indian Women as Depicted in Indian Fiction in English - Chatterjee, Monali (Margins/Marges/Margini, 2025)
Indian fiction in English prominently demonstrates the imposing presence of marginalisation founded upon gender. Gender Marginalisation is an extensively recognized social concern, accentuating the anguish of gender discrimination, oppression and subordination in all societies. For this research, two short stories by eminent Indian stalwart writers have been selected. Amrita Pritam (1919- 2005) is regarded as one of the forerunners of Indian women writers of the twentieth century. Her works asserting her identity in society have established her as a chief proponent of feminist writing. Her celebrated story “270 Crore Heartbeats” illustrates several gender marginalities that weigh down upon our society even today. In contrast to Pritam, Rabindranath Tagore (1861- 1941) also theorises through his literature some of the crucial gender-marginal concerns of his day that were governed by rigid social conditioning and are still prevalent in the present day. His short story, “Profit and Loss” demonstrates the hideous repercussions that spell havoc in the lives of people who that coerced to follow the male-dominated norms of society. Both these authors have been versatile visionary thinkers in their own right. Yet, their critique of social malpractices makes a strong statement in theorizing gender marginalities of society. This paper evaluates and contrasts how both these writers have flagrantly critiqued the social institution of marriage and how the marginalization based on gender can gnaw at the foundation of any society and destroy is cultural values of solidarity.